Perancangan Interior Hongkong Chinese Restaurant di Makassar - Patrick Wongso; Freddy Handoko Istanto; Maureen Nuradhi (KREASI, 2015)
Designing Hong Kong-Chinese Restaurant Interior in Makassar Business development in Makassar city is progressing swiftly, especially in property sector, thus leading to better life style. Withthe improving life style, it affects the society demand of better interior design adapted to the current trend. Therefore, interior design consultants play an important role and it is getting difficult to find a great consultant nowadays.With the accelerating growth in property sector as well as the life style of Makassar people, it creates an opportunity for Patrick Wongso Interior Consultant to establish an interior design consulting firm in Makassar. Patrick Wongso Interior Consultant provides interior design consultation service, which provide both professional and practical solution that incorporates the customer’s needs. Hong Kong Chinese Restaurant which takes place in Makassar city, is a restaurant which serves Chinese food, and seafood. Hong Kong Chinese Restaurant is located at Timor street no.69, Makassar. Hong Kong Chinese Restaurant provides facilities, such as family restaurant, VIP room, Bar, and multi-function hallfor reunion, and birthday party. The visitors of Hong Kong Chinese Restaurant are mostly from middle-upclass. This restaurant’s concept is based on the theme of elegantChinese nuance. This concept is appliedto the layout design, ceiling, wall, furniture, and floor in order to unify all the interior elements as well asstrengthening the desired concept.